Russian-speaking tour guide’s language mastery: mastering foreign language for quality service assurance - Gede Ginaya; I Wayan Jendra; Ida Zuraidah; I Ketut Sadia (Politeknik Negeri Bali, 2018)
A professional tour guide is regarded as a front-liner of the tourism and the ambassador of his/her country. Therefore, the performance of a tour guide is very important as a quality assurance of services in order to fulfil the tourists’ satisfaction. This study aims at investigating the mastery level of the tour guide’s Russian language related to the quality assurance of uniform services in meeting the tourists’ satisfaction. By applying a descriptive qualitative research, the data was collected through observation, interview, and document review. The theory used to undertake this study is communicative competence (grammar, sociolinguistics, and communicative strategic). The study reveals that the mastery of Russian language for a professional tour guide has been proven to meet the expectation of Russian tourists to get the excellent service as a quality assurance to provide the tourist satisfaction so that products prepared by travel agents and purchased by the tourist are carried out properly.